Is long duration aerobic exercise necessary for anaerobic athletes? - Murach, K.; Bagley, J. R.; Pfeiffer, C. J. Jr (Strength and Conditioning Journal, 2013)
Long duration aerobic exercise has long been a staple of training programs for both aerobic and anaerobic athletes. Without question, this mode of training has the potential to induce numerous physiological benefits which enhance metabolic and cardiovascular performance. However, much debate exists over whether or not anaerobic athletes are able to achieve these same adaptations through other forms of exercise. This questions the necessity of long duration aerobic exercise for these athletes. The following column will argue for (pro) and against (con) the need for anaerobic athletes to engage in long duration aerobic exercise. We want to hear from you. Visit nsca-scj.com to weigh in on the point/counterpoint quick poll.